Mechanical properties of organic–inorganic halide perovskites, CH3NH3PbX3 (X = I, Br and Cl), by nanoindentation1. Issue 36 (28th September 2015) - Sun, Shijing; Fang, Yanan; Kieslich, Gregor; White, Tim J.; Cheetham, Anthony K.
<x xml:space="preserve">Abstract</x> Trends in the Young's Modulus and Hardness for the hybrid perovskites CH3NH3PbX3 (X = I, Br and Cl) are assessed in relation to the underlying chemical bonding.